Penerapan Algoritma Rivest Shamir Adleman Untuk Meningkatkan Keamanan Virtual Private Network - Adiat Pariddudin; Muhammad Syawaludin (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
Data and information security of an organization or company is very important. Data in an organization or company has important information for the sustainability of a company, as well as PT Karya Gemilang Plasindo. In order to increase the productivity and speed of information data, a VPN (Virtual Private Network) technology was built to connect the branch company and some employees who work on a mobility. But in practice there is a gap in the VPN (Virtual Private Network) technology used, the management of devices and users is irregular because the connecting process is only a username and password. The solution is to increase security in VPN (Virtual Private Network) technology by changing the VPN (Virtual Private Network) protocol and adding a certificate to limit devices that can connect to the intranet network. Previously, VPN (Virtual Private Network) technology used the PPTP (Point-to-Point Tunneling Protocol) protocol. These deficiencies are solved by changing the protocol to SSTP (Secure Socket Tunneling Protocol) and creating a certificate as the identity of a device while limiting the devices that can connect to the intranet network. The design in this study used RnD (Research and Development) and the results were tested using the Validity Test and Reliability Test with the KR 20 technique (Kuder Richardson). This test is tested using a questionnaire about the level of security of the latest technology to users. The test results to be achieved are the increased security of VPN (Virtual Private Network) on the designed intranet network that is considered to be able to maintain data and information security at PT Karya Gemilang Plasindo